Evaluation of Moving Average Window Technique as Low-pass Filter in Microprocessor-Based Protecting Relays - Khodabakhshi-Javinani, N.; Askarian Abyaneh, H. (Engineering, Technology & Applied Science Research, 2017)
Over the last decades, with the increase in the use of harmonic source devices, the filtering process has received more attention than ever before. Digital relays operate according to accurate thresholds and precise setting values. In signal flow graphs of relays, the low-pass filter plays a crucial role in pre-filtering and purifying waveforms performance estimating techniques to estimate the expected impedances, currents, voltage etc. The main process is conducted in the CPU through methods such as Man and Morrison, Fourier, Walsh-based techniques, least-square methods etc. To purify waveforms polluted with low-order harmonics, it is necessary to design and embed cutting frequency in a narrow band which would be costly. In this article, a technique is presented which is able to eliminate specified harmonics, noise and DC offset, attenuate whole harmonic order and hand low-pass filtered signals to CPU. The proposed method is evaluated by eight case studies and compared with first and second order low-pass filter.